Unveiling communication strategies through public space signs: a linguistic landscape study in Badung Smart Heritage Market, Bali-Indonesia - Ketut Widya Purnawati; Ketut Artawa; Made Sri Satyawati; I. Nyoman Kardana (Cogent Arts & Humanities)
This study highlights the communication strategies used in outdoor signage at the Badung Smart Heritage Market in Bali, Indonesia, exploring the factors influencing language choices and how these signs interact with local cultural identity to shape visitor experiences. Data was collected through observation, photographic documentation, and interviews, which were analyzed qualitatively. The results show that the market fosters cultural awareness, strengthens community ties, and enhances tourism competitiveness. Although dominated by Indonesian and English, the Balinese script and language remain vital in expressing local identity. The Badung Smart Heritage Market presents opportunities to preserve and promote cultural heritage through creative communication strategies. These markets can become valuable assets for local communities and tourism with thoughtful approaches. To enhance signage in Badung Smart Heritage Market, stakeholders can create multilingual, visually clear, culturally reflective signs that engage and inform. Incorporating adaptable designs, interactive QR codes, and co-branded signage with local businesses can ensure sustainable, accessible navigation that celebrates Bali’s heritage while meeting diverse visitor needs.